1998
DOI: 10.1111/j.1432-2277.1998.tb01164.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of N-acetylcysteine as a hepatoprotective agent in liver transplantation

Abstract: One of the most common complications after liver transplantation is primary graft dysfunction which results from severe deterioration of the microcirculation. The data obtained from our experimental studies indicate that N-acetylcysteine (NAC) is able to reduce the severity of ischemia/reperfusion injury and improves postoperative graft function after liver transplantation in rats. The aim of this pilot study was to evaluate the efficacy of NAC as a hepatoprotective agent under clinical conditions. A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…These authors have concluded that the opening of arteriovenous shunts and the diversion of blood away from the gastrointestinal tract might cause hypoxia. Thies et al [20] observed significantly better portal vein flow in transplanted patients treated with NAC. In the study of Schmidt et al [21], treatment with NAC increased the mesenteric postcapillary flow of the rabbits that received E. coli lipopolysaccharides.…”
Section: Discussionmentioning
confidence: 96%
“…These authors have concluded that the opening of arteriovenous shunts and the diversion of blood away from the gastrointestinal tract might cause hypoxia. Thies et al [20] observed significantly better portal vein flow in transplanted patients treated with NAC. In the study of Schmidt et al [21], treatment with NAC increased the mesenteric postcapillary flow of the rabbits that received E. coli lipopolysaccharides.…”
Section: Discussionmentioning
confidence: 96%
“…4,20 Following encouraging results about the effectiveness of NAC against hepatic ischemia/reperfusion injury in animals with a healthy liver, NAC has been reported to reduce ischemia/reperfusion injury and improve graft function after liver transplantation in humans too. 11,21 However, ischemia/reperfusion injury in a steatotic liver differs from that in a normal liver, with massive necrosis, or uncontrolled cell death, occurring instead of controlled apoptosis. The release of cytoplasmic contents and infl ammation causing systemic injuries such as acute tubular necrosis adversely affects the survival of rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NAC increases liver blood fl ow and has hepatoprotective effects on hepatic ischemia-reperfusion injury by improving hepatic macro-and microcirculation. 10,11 This suggests that NAC could improve impaired regeneration capacity in NAFLD. The antioxidative properties of NAC have been the subject of experimental studies on the treatment of NAFLD, with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…N-acetylcysteine, especially at high doses, has been successful in preserving microcirculatory function in some studies but has been ineffective in others (28,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). In a pilot clinical study, it also seemed to improve outcomes in patients (46). A P-selectin antibody has been effective, presumably by preventing or reducing leukocyte infiltration (47).…”
Section: Discussionmentioning
confidence: 99%